Indonesian L2 Learners’ Resilience and Self-directed Learning In Online Classes: A Correlational Study - Adaninggar Septi Subekti (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
The present study aimed to investigate Indonesian second language (L2) learners’ level of resilience and the relationship between their resilience and their self-directed learning (SDL) in an online learning setting at the time of the Covid-19 pandemic. The present study used a survey method by distributing Google Form questionnaires. The participants were 187 university student participants taking English for Academic Purposes (EAP) classes online in their respective departments. It was conducted to fill the void in resilience literature in the Indonesian L2 context and to find out the Indonesian learners’ resilience in the online learning setting as well as to know whether learners’ resilience was associated with their SDL, a critical element to succeed in online learning. The study found that learners possessed a high level of resilience. Learners were found to have a high level of realistic optimism and self-discipline, prominent characteristics of resilience. However, they reported a slightly lower level of capability in handling multiple tasks at the same time. The study further found that learners’ resilience was significantly, moderately, and positively correlated with their SDL. Based on the findings, possible contributions and implications are stated alongside the limitations of the study and possible directions for future research.